CamKII inhibitors reduce mitotic instability, connexon anomalies and progression of the in vivo behavioral phenotype in transgenic animals expressing a mutated Gjb1 gene - Mones, Saleh; Bordignon, Benoit; Peiretti, Franck; Landrier, Jean F.; Gess, Burkhardt; Bourguignon, Jean J.; Bihel, Frédéric; Fontés, Michel (Frontiers in Neuroscience, 2014)
Mutation in the Gjb1 gene, coding for a connexin (Cx32), is associated with an inherited peripheral neuropathic disorder (X-linked Charcot-Marie-Tooth, CMTX). Our previous work reported that transgenic animals expressing a human Gjb1 transgene present polyploidy and abnormal over-duplication of the centrosome, suggesting a role for Gjb1 in mitotic stability. In this article, we propose mechanisms by which mutations in Gjb1 induce mitotic instability and discuss its potential relation with the CMTX phenotype. We showed that transgenic cells exhibit CamKII over-stimulation, a phenomenon that has been linked to mitotic instability (polyploidy, nuclear volume and centrosome over-duplication), that is reversed by CamKII inhibitors. We also demonstrate that connexon activity is partially restored in transgenic cells with CamKII inhibitors. Our model supports the role for Pim1, a kinase that has been associated with genomic instability in cancers, in genomic instability in Cx32 mutations. Regarding in vivo phenotype, we showed that degradation on the rotarod test in our transgenic mice is significantly lowered by treatment with a CamKII inhibitor (KN93). This effect was seen in two lines with different point mutations in GJB1, and stopping the treatment by KN93 led to degradation of the phenotype.